Beyond rich and poor: Identifying global development constellations - Christine Hackenesch; Svea Koch; Sebastian Ziaja (Development Policy Review, 2022)
Motivation The COVID-19 pandemic is the most recent instance of global development problems being liable to occur anywhere, challenging the assumption of a world divided into "developed" and "developing" countries. Recent scholarship has increasingly opted for the term "global development" to capture this changing geography of development problems. Purpose Our article contributes to these debates by proposing a novel empirical approach to localize global development problems in country contexts worldwide. Methods and approach Our approach rests on a universal understanding of "development." We identify countries that are particularly relevant for global problem-solving and consider not only the problem dimension but also countries' capacities to address these problems. Findings Our results show that countries with the most severe combinations of problems cover a range as broad as Afghanistan, Nigeria, and the United States. Two thirds of countries with above-average contributions to global problems are governed by authoritarian regimes. We also find that middle income countries, whether lower-middle or upper-middle as defined by the World Bank, have little in common apart from their income level. Policy implications Our analysis shows that traditional development concepts of a binary world order and of foreign aid as financial transfer to remedy imbalances are not enough to address constellations of global problems and capacity that have long evolved beyond rich and poor.
Keywords: 300; environmental degradation; global development; international development; poverty; violence